FOCUS ON ECOLOGY AND THE ONGOING RENEWAL OF MORAL THEOLOGY - Biju Michael (Asian Horizons, 2015)
This article focuses on the increased attention given by Moral Theology to the issues of ecology and the environmental crisis faced by the contemporary society. It tries to see how this increased focus is an integral part of the ongoing renewal of moral theology, which, according to the instruction of Vatican II, tries to answer current issues facing human beings with the help of the light of revelation and in the context of the faith in its integrity. It focuses on the history of the increased attention, the identification of the root cause of the crisis as a moral problem and proceeds to propose solutions in the light of faith.